Impact of acute and chronic cycling exercise on microvascular reactivity of the upper and lower extremity muscles in young healthy females - Xuanyao Liu; Bin Leng; Haizhen Huang; Yadan He; Chuan Zhang (Journal of Exercise Science & Fitness)
Background: Few studies have evaluated the impact of exercise on specific skeletal muscle microvascular function, despite its importance. This study aimed to assess the acute and chronic effects of cycling exercise on microvascular reactivity in the upper and lower extremities of young healthy females. Methods: Eighteen young healthy females performed an acute bout of cycling exercise on a cycle ergometer at 75 % of their maximal heart rate for 30 min, both before and after cycling training three times a week for eight weeks. For each bout of acute exercise, microvascular function in the biceps brachii (BB) and vastus lateralis (VL) muscles was assessed using near-infrared spectroscopy coupled with the post-occlusive reactive hyperemia technique, measured pre-exercise and at 20-, 40-, and 60-min post-exercise. Body composition was assessed using dual-energy X-ray absorptiometry before and after training. Results: Total body fat mass, abdominal fat mass and leg fat mass were significantly reduced by training. Before training, cycling exercise acutely improved microvascular reactivity in BB but not in VL. Eight weeks of cycling training significantly improved resting microvascular reactivity in BB but not in VL. Training had no impact on post-exercise microvascular reactivity at VL, but elicited improvement in BB. Conclusions: Acute and chronic cycling exercise enhanced skeletal muscle microvascular responses in the upper extremity of young healthy females, but this effect was not observed in the lower extremity. Training enhanced post-exercise microvascular responses at upper extremity but not lower extremity.